Hong Kong Global China's Restive Frontier - Kwan Lee, Ching (Social Sciences, 2022)
CK Lee situates the post-1997 China-Hong Kong contestation in the broader context of 'global China.' While Beijing deploys numerous power mechanisms globally, this Chinese power project has triggered countermovements from Asia to Africa. Hong Kong, stunning and singular in its many peculiarities, offers lessons about China as a global force.